Sensitive and selective detection of peanut allergen Ara h 1 by ELISA and lateral flow immunoassay. (1st December 2022) - Hnasko, Robert M.; Lin, Alice V.; McGarvey, Jeffery A.; Mattison, Christopher P.
Highlights: Sensitive and specific immunoassays detect the peanut protein Ara h 1. On-the-go detection of peanut protein in foods by lateral flow immunoassay. Novel peanut detection technologies improve food safety. Abstract: The Ara h1 protein is a peanut allergen and it provides a useful biomarker for the detection of peanut protein. In this manuscript, we describe the generation of monoclonal antibodies (MAbs) against the Ara h1 protein and their development into sensitive and selective immunoassays for peanut detection. Our enzyme-linked immunosorbent assay (sELISA) detects a peanut meal standard with a sensitivity of 10 ng/mL and 500 ng/mL by lateral flow immunoassay (LFIA). MAb Ara h1 binding epitopes were identified, and immunoassay detection was limited to peanut meal varieties irrespective of thermal treatment. No binding was observed from tree nut meals (100–0.4 µg/mL). Peanut allergen detection during food manufacturing can limit the incidence of product recall resulting from cross-contact contamination or improper labeling of finished food products. Detection of Ara h1 by immunoassay can provide a cost-effective method for rapid surveillance of peanut during food production and prior to consumption.